# Write the equation in standard form. Then factor the left side of the equation.3x2 + 19x = 14A (3x

###### Question:

A (3x + 2)(x – 7) = 0

B (2x – 3)(x + 7) = 0

C (2x + 3)(x + 7) = 0

D (3x – 2)(x + 7) = 0

## Answers

2x^2 = 28 - x in standard form is 2x^2 + x = 28

Factoring, we have:

x(2x + 1) = 28

3x^2+19x-14=0 Standard form

(3x-2)(x+7)=0 Factored

4x+7×=15 think thats the right answer

[tex]given \: equation - - - \\ 2 {x}^{2} + 7 x = 15 \\ \\ standard \: form - - - \\ 2 {x}^{2} + 7x - 15 = 0 \\ \\ factorising \: left \: side - - - \\ \\ = 2 {x}^{2} + 7x - 15 \\ \\ = 2 {x}^{2} + 10x - 3x - 15 \\ \\ = 2x(x + 5) - 3(x + 5) \\ \\ = (x + 5)(2x - 3)[/tex]

C. (2x – 3)(x + 5) = 0

Step-by-step explanation:

The equation in standard form should be 2x^2 + 7x - 15 = 0

Factored the expression is (2x - 3)(x + 5).

In order to find the factored portion, you must look for factors of the front number (2) to use in the front of the parenthesis and factors of the last number (-15) to go in the end.

When we use the ones that we have above, it distributes to the overall end result.

(2x - 3)(x + 5)

2x^2 - 3x + 10x - 15

2x^2 + 7x - 15

[tex]17. Write the equation in standard form. Then factor the left side of the equation. 2x2 + 7x = 15[/tex]

2x^2 + 7x - 15 = 0

Factors: (2x - 3)(x + 5)

Step-by-step explanation:

To write the equation in standard form rearrange to this form ax^2 + bx + c = 0. Rearrange the equation 2x^2 + 7x = 15 by subtracting 15 from both sides.

2x^2 + 7x - 15 = 0

The left side factors into (2x - 3)(x + 5) since it multiplies to 2x^2 - 3x + 10x - 15 = 2x^2 + 7x - 15.

2x² = 28 - x

2x²+x-28=0

2x²+8x-7x-28=0

2x(x+4)-7(x+4)=0

(x+4)(2x-7)=0

(2x-7)(x+4)=0

B.) (2x - 7)(x + 4) = 0

Standard form of the equation, [tex]3x^2+19x-14=0[/tex]

Factor of the equation is, [tex](x+7)(3x-2)=0[/tex]

Step-by-step explanation:

The standard form of the quadratic equation is given as

[tex]Ax^2+Bx+C = 0[/tex]

Given the equation:

[tex]3x^2+19x = 14[/tex]

Subtract 14 from both sides we have;

[tex]3x^2+19x-14=0[/tex]

⇒The standard form of the equation is, [tex]3x^2+19x-14=0[/tex]

Now, find the factor of the given equation:

[tex]3x^2+19x-14=0[/tex]

⇒[tex]3x^2+21x-2x-14=0[/tex]

⇒[tex]3x(x+7)-2(x+7) = 0[/tex]

⇒[tex](x+7)(3x-2)=0[/tex]

Therefore, the factor of the equation is, [tex](x+7)(3x-2)=0[/tex]

Answers to Write the equation in standard form. Then factor the left side of the equation. 2x^2 + 7x ...standard form is ax^2 + bx + c=0 2x^2 + ... (2x - 3)(x + 5) = 0

C (2x-3)(x+5). I just know. Please give me the brainliest